Ethno-learning as a character education strategy: integration of local culture in cirebon schools - Cahyaningsih, Ade; Nurdin, Encep Syarief; Budimansyah, Dasim; Ruyadi, Yadi (Universitas Tanjungpura, 2025)
This study aims to examine the implementation of ethno-learning as a character education strategy through the integration of local Kacirebonan cultural values in government-based secondary schools in Cirebon City. Using a multi-site ethnographic approach, this study was conducted for one year in four schools that actively develop culture-based learning. The results of the study indicate that ethno-learning is implemented in two main forms, namely through the integration of local culture in intracurricular subjects and through extracurricular activities such as mask dance, gamelan, rebana, and the